2016
DOI: 10.1093/mnras/stw781
|View full text |Cite
|
Sign up to set email alerts
|

Modelling the structure of molecular clouds – I. A multiscale energy equipartition

Abstract: We present a model for describing the general structure of molecular clouds (MCs) at early evolutionary stages in terms of their mass-size relationship. Sizes are defined through threshold levels at which equipartitions between gravitational, turbulent and thermal energy |W | ∼ f (E kin + E th ) take place, adopting interdependent scaling relations of velocity dispersion and density and assuming a lognormal density distribution at each scale. Variations of the equipartition coefficient 1 f 4 allow for modellin… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 62 publications
1
11
0
Order By: Relevance
“…A similar range of values is obtained from observations of molecular clouds. Hennebelle & Falgarone (2012) showed that, when compiled, the observational results are compatible with a variation of the exponent with R, i.e., non-power-law behavior, a feature that was also noticed in numerical simulations (Veltchev et al 2016).…”
Section: Mass-size Relationsupporting
confidence: 64%
“…A similar range of values is obtained from observations of molecular clouds. Hennebelle & Falgarone (2012) showed that, when compiled, the observational results are compatible with a variation of the exponent with R, i.e., non-power-law behavior, a feature that was also noticed in numerical simulations (Veltchev et al 2016).…”
Section: Mass-size Relationsupporting
confidence: 64%
“…Traditionally, the apperent near-virialization exhibited by clouds and their substructures (clumps and dense cores) been interpreted as a manifestation that all the structures in this hierarchy are supported against their selfgravity by strongly supersonic turbulence, and that, when this turbulence dissipates at the smallest scales, the cores can then proceed to collapse (see, e.g., the reviews by Larson 1981;Vázquez-Semadeni et al 2000;Mac Low & Klessen 2004;Ballesteros-Paredes et al 2007;McKee & Ostriker 2007;Bergin & Tafalla 2007;Hennebelle & Falgarone 2012;Dobbs et al 2014;Donkov et al 2011Donkov et al , 2012Veltchev et al 2016). However, it is difficult to understand how the many energy-injection mechanisms could adjust themselves to provide just the right amount of energy to the turbulence to keep the structures nearly virialized at all scales.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the study of star formation requires an understanding of the morphological and kinematical evolution of MCs. This evolution could be traced, e.g., through the physical parameters of cloud fragments (clumps, cores, filaments) and their scaling relations (Heyer et al 2009; Larson 1981; Solomon et al 1987; Veltchev et al 2018) or by investigation of the general cloud structure in terms of abstract scales (Dib et al 2020; Donkov et al 2017; Heyer & Brunt 2004; Stutzki et al 1998; Veltchev et al 2016).…”
Section: Introductionmentioning
confidence: 99%